Identification of Zika virus in immature phases of Aedes aegypti and Aedes albopictus: a surveillance strategy for outbreak anticipation - Maniero, V. C. (2019)
Universidade do Grande Rio. Departamento de Saúde. Programa de Pós-graduação em Biomedicina Translacional. Duque de Caxias, RJ, Brasil.